ANALISIS KINERJA KEUANGAN BADAN USAHA MILIK NEGARA(BUMN) PASCA PRIVATISASI - Abubakar Arif; Husein Ukassa (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2010)
This research was aimed to know the financial's performance of state company (BUMN) before and after privatized, so that it could be known whether privatizes was the right solution to fix BUMN'S perfonnance. This observational data acquired from BUMN's corporate which was privatized upon year 2002 by Initial Public Offering's methods (IPO), the firms among those were PT. Kimia Farma Tbk. , PT. Indofarma Thk. , PT. Tambang Batubara Bukit Asam Tbk. , and PT. Perusahaan Gas Negara Thk The sample on this research was the financial performance of BUMN's corporate which was privatized with time interval of three years (period) before and after privatizes. The financial performance measured by eight indicators, that amongst those: Return On Equity (ROE), Return On Investment (ROI), Cash Ratio, Collection Periods, Inventory Turn Over, Full scale Revaluation Turn Over, Equities Totaled ratio to Full Scale Revaluation. The analysis's method data that is utilized is one sample ofKolmogrov Smirnov, and Paired Samples Test. The results of the analysis found that BUMN's financial performance which privatized by IPO method was not made much progress, even some indicator of finance's performance decreased. It even bastioned by yielding hypothesizing examination that shows that there were not differentiate and poor relationship in finance's performance before and after privatized. However, privatizes is supposed to not only aims to close deficit RAPBN, but in long-term the managements of corporate performance shall get to show openness, independence, naturalness, and accountabilities to reach good corporate governance. Nevertheless, in world trade there are just a firm that have good performance will gets to pull investor candidate to imbed its capital